The Isolation of mercury-resistant bacteria in the Brantas River, Malang, Indonesia - Harmoko, Deni (Svāsthya: Trends in General Medicine and Public Health, 2025)
Mercury (Hg) is a toxic heavy metal that can originate from various sources, such as gold mining, the industrial sector, atmospheric deposition, and natural activities. Mercury contamination can cause liver, kidney, and enzyme system damage, as well as DNA damage. Because microorganisms are more sensitive to heavy metal stress than are animals and plants, the characteristics of microorganisms can be potential indicators of environmental health. This study aimed to isolate and identify mercury-resistant bacteria in the Brantas River, Malang as potential indicators of Hg pollution. Samples were isolated on nutrient agar (NA) media supplemented with 0.01 ppm HgCl₂ as a selective medium. The growing bacterial colonies were purified, and further resistance tests were carried out by adding HgCl₂ at concentrations of 0.03 ppm, 0.05 ppm, and 0.1 ppm. Bacterial isolates that survived at a concentration of 0.1 ppm HgCl₂ were then tested for sensitivity to concentrations of 0.15 ppm and 0.2 ppm HgCl₂. Bacterial isolation via HgCl₂ 0.01 ppm selective media produced 28 bacterial isolates. Further testing revealed that 19 isolates were resistant to 0.03 ppm HgCl₂, 13 isolates (0.05 ppm), and five isolates (0.1 ppm. Sensitivity tests on five bacterial isolates revealed that at a HgCl₂ concentration of 0.15 ppm, isolates RS118, RS1221, and RS1323 showed no growth inhibition, whereas at a concentration of 0.2 ppm, an inhibition zone formed for all five isolates. Although mercury-resistant bacteria were detected, this finding does not directly indicate the presence of mercury pollution in the river because bacterial resistance can be caused by various factors, including horizontal gene transfer between bacterial communities. Comprehensive testing of Hg concentrations in rivers is required to accurately determine the status of Hg pollution. This study highlights the importance of considering multiple biomarkers and environmental parameters alongside bacterial resistance patterns when assessing Hg contamination in riverine ecosystems.